Analysis of urban public spaces’ wind environment by applying the CFD simulation method: a case study in Nanjing - Wang, Xiaoyue; Liu, Fang; Xu, Zhen (Geographica Pannonica, 2019)
The increase in the density of high-rise buildings is making urban air flow increasingly complex, and the wind environment conditions in urban public spaces are considerably changing. At present, few studies focus on the relationship between wind environment and the master plan of urban public spaces or attempt to improve the wind environment of public spaces from a landscape design perspective. To resolve this gap in information, this study explored the relationship among wind speed, seasonal comfort level in Nanjing, and different types of planting patterns. Computational fluid dynamics (CFD) software was used to quantify the seasonal wind environment of Xuanwumen Square in Nanjing. Three planting designs were created on the basis of the results, and their CFD results were compared among one another. Comparison results show that the second planting design provides the best wind environment, and its comfort levels are 2.26, 1.92, and 2.09 out of 5 in winter, summer, and total. Understanding of the relationship among different landscape designs and their impacts on wind environment supports designers in improving the wind environment of Xuanwumen Square in Nanjing. This study provides new insights into relating urban public space design with the quantitative research of wind environment in the future.